Modelling of strategies for the introduction and routine use of multivalent meningococcal conjugate vaccines (MMCVs) in the African meningitis belt - Andromachi Karachaliou Prasinou; Caroline Trotter (PLoS ONE, 2025)
The introduction of MenAfriVac has significantly reduced group A meningococcal meningitis in the African meningitis belt, but epidemics caused by other groups such as C, W, Y and X (MenCWYX) remain a threat. To address this, a new multivalent meningococcal conjugate vaccine (MMCV) has been developed and pre-qualified by WHO. This study extends a previously established transmission dynamic model for MenA to include MenCWYX, enabling evaluation of the potential impact of MMCVs under various vaccination strategies. Using Burkina Faso as a case study, the model simulates mass campaigns targeting different age groups and routine vaccination through the Essential Programme on Immunization (EPI). The results indicate that campaigns targeting 1–29-year-olds are most effective in averting cases and delaying disease resurgence, while 1–19-year-old campaigns offer a resource-efficient alternative. Vaccine efficacy against carriage and the duration of protection significantly influence outcomes; greater efficacy (90% vs. 60%) and longer protection delay resurgence and reduce the number of cases. Routine- only vaccination demonstrates value in lower-risk settings, though it is less effective than combined strategies. Sensitivity analyses confirm the robustness of the ranking of strategies but highlight the importance of accurate estimates of vaccine efficacy and transmission parameters. The findings suggest that countries in the meningitis belt should integrate MMCVs into their immunisation programs, with high-risk countries prioritising catch-up campaigns for children and young adults. Despite data limitations and uncertainties, this model provides valuable insights for optimising vaccine rollout and highlights critical research needs, such as understanding vaccine effectiveness against carriage. These results support informed decision-making to sustain progress against meningitis and protect populations from future epidemics. MMCVs hold great promise in further reducing meningitis burden and approaching disease elimination in the region.